Validity and Reliability of Thai version of International Consultation on Incontinence Questionnaire Nocturia Module (ICIQ-N) and International Consultation on Incontinence Questionnaire Nocturia Quality of Life Module (ICIQ-Nqol) - Inta, Rujirada; Nuanthaisong, Umaphorn (The Bangkok Medical Journal, 2024)
OBJECTIVES: To evaluate the validity and reliability of the Thai version of ICIQ-N and ICIQ-Nqol. MATERIALS AND METHODS: Descriptive study, the English version of the ICIQ-N and ICIQ-Nqol were translated to Thai, Back-translations, evaluated by Urologist experts and calculated IOC for validity assessment. Then 284 subjects in Vajira hospital were randomly selected for test-retest method, twice, two weeks apart for reliability evaluation. RESULTS: Completed data were obtained from 249 subjects. Their mean age was 37.7 ± 12 years old and 88 % of subjects were female. Most subjects were hospital personnel accounting for approximately 92.8% that complete questionnaires. The overall validity from index of item-objective congruence (IOC) ranged from 0.67-1.0. The internal consistency was strong in ICIQ-Nqol with Cronbach alpha = 0.937 and 0.938, respectively and moderate in ICIQ-N with Cronbach alpha = 0.677 and 0.653, respectively. The test-retest reliability of ICIQ-N and ICIQ-Nqol with Pearson product-moment correlation showed Coefficient of Stability close to 1 in both (r = 0.81, r = 0.92, respectively, p < 0.001) (statistically significant with p < 0.001 level and ≥ 0.5 values). CONCLUSION: ICIQ-N and ICIQ-Nqol have good content validity and convergent validity. There is a strong internal consistency in ICIQ-Nqol but moderate in ICIQ-N. And they have excellent test-retest reliability. Therefore, these questionnaires can be used to evaluate nocturia problems in Thailand patients.